2000
DOI: 10.1243/0957650001538029
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in the prediction of performance of centrifugal slurry pumps handling slurries

Abstract: A methodology based on a loss analysis procedure has been presented to predict the performance of centrifugal slurry pumps handling solid-liquid mixtures. Various energy-head losses in the pump have been estimated using analytical models based on the pump geometry and the properties of suspended solids. The proposed methodology accounts for the constructional differences of the slurry pump as compared with the conventional pump. The predicted values of head over the operating range of flowrates of the pump hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 9 publications
(23 reference statements)
2
9
0
Order By: Relevance
“…as the solid concentration of suspension increases, a relatively larger numbers of solid particles increases in the suspensions hence a large value of shear stress (particle-fluid and particle-particle) is required to start the shearing process. similar observation also drawn by [1,14,19,20] with fly ash slurry.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…as the solid concentration of suspension increases, a relatively larger numbers of solid particles increases in the suspensions hence a large value of shear stress (particle-fluid and particle-particle) is required to start the shearing process. similar observation also drawn by [1,14,19,20] with fly ash slurry.…”
Section: Resultssupporting
confidence: 89%
“…it is found that the proportion of al 2 shows that these particles have high surface enrichment of al/si. high surface enrichment of al/si indicates that these particles causing drag effects on the flow behavior of the fly ash slurry [18][19][20]. Particle size distribution of bottom ash sample was evaluated using sieve analysis method.…”
Section: Properties Of Bottom Ashmentioning
confidence: 99%
“…A Perspex pipe (8) is placed at the end of the pump delivery piping system to visualize the pu mp output flow mixture. Pu mp flow rate is measured using turbine flow meter (7). A frequency inverter is emp loyed in order to have the ability to control and varied the pump operating speed, if needed.…”
Section: Experimental Apparatus and Instrumentationmentioning
confidence: 99%
“…Sellg ren et al [6] showed that the addition of clay to sand slurries has been found to reduce the pipeline friction losses, thus lowering the required energy consumption. Gandhi et al [7] presented a methodology based on a loss analysis procedure to predict the performance of centrifugal slurry pu mps handling solid-liquid mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that the addition of clay to sand led to a reduction in pipe line friction losses, thus lowering the pumping head and power consumption. Gandhi, et al [12] developed a methodology based on a loss analysis procedure to predict the performance of centrifugal pumps handling slurries. Their methodology accounts for the constructional differences of the slurry pump when compared with the pure liquid pump.…”
mentioning
confidence: 99%